Hip fracture incidence among elderly Hispanics. - Lauderdale, D S (1998)
OBJECTIVES: This study estimated hip fracture incidence for elderly Hispanics in the United States. METHODS: A cohort of Spanish-surnamed 1992 Medicare enrollees was followed for 2 years. Hip fractures were identified by inpatient diagnostic code. RESULTS: For Hispanic women, the national age-adjusted hip fracture rate was 7.3 per 1000 person-years; for men, the rate was 3.3. Rates varied markedly, with higher rates for the predominantly Mexican-American southwestern states than for Puerto Ricans. CONCLUSIONS: Nationally, the Hispanic population is at intermediate risk of hip fracture between Blacks and Whites, but geographic variation suggests that Mexican Americans are at higher risk than Puerto Ricans.